Islamic Economics and Politico-Legal Policy: Defining The Fundamental Role of Government In Creating Prudential Business System - Abdillah, Abdillah; Ridho, Ali; Muslimin, JM; Munawar, Wildan; Elkushli, Salem Ahmed A (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to examine in depth the role of the government in stabilizing, allocating and distributing nation-wealth by minimizing monopoly from Islamic economics views as well as contemporary legal practices. The research method used is phenomenological-qualitative and empirical legal study. Data collected by observing the models formulated by fiqh experts and their implications for economic justice based on literature studies and empirical practices. The findings prove that in the discourse of fiqh and Islamic history, the government has strategic position in combating monopoly by its intervention in overcoming unfair economic practices. It has supreme political power and strong duty to create nation-welfare by paving the way towards social prosperity based on religious moral principles. The duty of government to stabilize, allocate and distribute nation-wealth must run on the notions of social justice and fair treatment for all. The existing rules of anti-monopoly may be compared and referred. The arguments that are in line to the conclusion: First, the historical facts at the beginning of Islam are in conformity of such a model. Second, there are some supportive legal arguments of fiqh scholars and existing present example. From these findings, it can be concluded that the study of Islamic economics has an important contribution in encouraging the role of the government to overcome the practice of monopolistic behavior or unfair business practices. In practical sense, such a policy must be realized in the type of checked and balanced social system that lead to social justice and good governance.